2002
DOI: 10.1086/342180
|View full text |Cite
|
Sign up to set email alerts
|

Planetary Nebulae as Standard Candles. XII. Connecting the Population I and Population II Distance Scales

Abstract: We report the results of [O III] λ5007 surveys for planetary nebulae (PNe) in six galaxies: NGC 2403, NGC 3115, NGC 3351, NGC 3627, NGC 4258, and NGC 5866. Using on-band/off-band [O III] λ5007 images, as well as images taken in Hα, we identify samples of PNe in these galaxies and derive their distances using the planetary nebula luminosity function (PNLF). We then combine these measurements with previous data to compare the PNLF, Cepheid, and surface brightness fluctuation (SBF) distance scales. We use a samp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
396
1
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 241 publications
(430 citation statements)
references
References 99 publications
31
396
1
2
Order By: Relevance
“…The prompt SNIa component (which represents 50% of the SNIa population) discussed by Mannucci et al (2006) (2000) observed several high-ionisation "clouds" in this area. These authors discussed that the intensity of 3 of these sources is much larger than those of planetary nebulae detected in M 31 by Ciardullo et al (2002). However, in this central region, it might be possible that these sources are multiple.…”
Section: Ionised Gasmentioning
confidence: 98%
“…The prompt SNIa component (which represents 50% of the SNIa population) discussed by Mannucci et al (2006) (2000) observed several high-ionisation "clouds" in this area. These authors discussed that the intensity of 3 of these sources is much larger than those of planetary nebulae detected in M 31 by Ciardullo et al (2002). However, in this central region, it might be possible that these sources are multiple.…”
Section: Ionised Gasmentioning
confidence: 98%
“…In Sect. 3 we present the observational data used in this work, the Very Large Array (VLA) maps at 1.4 GHz and 4.8 GHz Fletcher et al (2011), LOw Frequency ARray (LOFAR) map at 151 MHz (Mulcahy et al 2014), and our new GMRT map at Tully (1974); (b) Ciardullo et al (2002); (c) Bigiel et al (2010).…”
Section: Introductionmentioning
confidence: 99%
“…The first of these is a "dip" in the luminosity function which starts ∼ 2 mag below M * . This feature is not present in every galaxy: in M31, the faint-end of the PNLF is well described by the simple Henize & Westerlund (1963) exponential, which is expected from an ensemble of uniformly expanding spheres ionized by non-evolving central stars (Ciardullo et al 1989(Ciardullo et al , 2002. However, as Figure 2 illustrates, star-forming systems such as the Small Magellanic Cloud and M33, have a factor of ∼ 2 fewer PNe than predicted from the exponential law (Jacoby & De Marco 2002;Ciardullo et al 2004).…”
Section: The Photometric Regimementioning
confidence: 94%
“…For example, PNe in the Milky Way exhibit a wide range of excitation, with [O III] λ5007 to Hα emission line ratios (R) ranging from ∼ 4 to ∼ 0.1. However, when one studies extragalactic PNe, a pattern emerges: the brightest PNe all have R > 2, regardless of their parent stellar population (Ciardullo et al 2002). In fact, the best way to analyze the bright emission lines from a homogeneous PN dataset is through a differential, multi-dimensional analysis.…”
Section: The Bright-line Regimementioning
confidence: 99%